Microestrutura e deformação a quente de um aço dinx20cr13 na laminação de tubos sem costura - Meire Guimaraes Lage (2008)
The DIN X20Cr13 stainless steel is a high technological alloy usually used in oil industry for onshore and offshore tubing applications. In this study DIN X20Cr13 equilibrium diagrams were made by Thermo-Calc software to study transformation reactions in solid state phases. This stainless steel was submitted to different heat treatments in order to generate delta ferrite to characterize and quantify it. Hot torsion tests were made to study DIN X20Cr13 mechanical properties and softening kinetic. The results showed that polygonal delta ferrite was not built with quantity enough to damage DIN X20Cr13 steel mechanical properties during the rolling process seamless steel tubes. The ferrite originated from the decarburized austenite could be related to the damage on DIN X20Cr13 mechanical properties by promoting wrinkles in seamless steel tubes. The hot deformation equation and the peak stress equation for DIN X20Cr13 could be described in this study